Cabaran Dakwah Islam di Era Siber - Abd. Ghani, Zulkiple (Jurnal Usuluddin, 2002)
This article seeks to discuss the challenges faced by Islamic dakwah in the era of cyberspace. It begins with an exploration of the changing space aerated by the new information technologies, which rely on the idea that information is a commodity. It also presents Islamic perspectives on managing Islamic massages by a proper control on the access of information; verify the credibility of sources; and the structure of Islamic contents that are suit able with the new technologies. The writer argues that Muslim preachers should be aware of the consequences of cyberspace development and should design Islamic messages accurately in order to compete and ensure that dakwah is always preeminent in the life of Muslims.